Assessment of pantograph-catenary interaction in a railway overlap section via a novel optical-based method. (November 2022) - Jiang, Tengjiao; Frøseth, Gunnstein T.; Nåvik, Petter; Rønnquist, Anders
Highlights: Pantograph-catenary interactions at an existing overlap span are investigated. A novel optical-based method is proposed and implemented at the overlap span. Single- and double-pantograph train passages are obtained and studied. Dynamic effects rendering high contact forces, contact loss and arcing are studied. Peak contact force, transition distance and train speed show a strong correlation. Abstract: Smooth pantograph-catenary contact is essential for regular train operation. However, catenary section overlaps are locations where peak contact forces occur, which significantly affects current collection quality. This work studies pantograph-catenary interaction and transition at an existing overlap span by using a novel optical-based measuring method. Image sequences of eleven single- and two double-pantograph train passages were processed to obtain wire displacement responses. The unsynchronised vibration of two contact wires was found, and the first contact wire exhibits different modal responses. The spatial motion paths of contact wires were obtained to estimate the pantograph-catenary interaction. Dynamic effects rendering high contact forces, contact loss and arcing were investigated. The results show that pantographs with a long transition distance and a high intersection gradient cause a serve impulse with the second contact wire, resulting in contact loss and arcing. Finally, this study successfully estimated the transition distance and found it has a strong positive correlation with peak contact forces and train speeds. The transition distance exhibits an increasing tendency with increasing train speed. The longer transition distance results in a higher peak contact force.